Comprehensive Analysis of Emerging Trends in Public Health and Policy - Albalawi, Yasir Mohammad Ateeg; Alshawwamiyyan, Muflih Hammad Sulaiman; Albalawi, Subhi Ateeq Aodah; Albalawi, Murdhi Sulaman Hamdan; Albalawi, Khaled Hdear Mushahhin; Albalwi, Mohammed Faraj Hamoud; Alanazi, Kareem Atallah Obaid; Alatawi, Mohamme Muter Mohammed; Alhewti, Ahmad Ali Mhamad; Alfaidi, Rimah Hammad Sultan (Journal of Ecohumanism, 2024)
New trends in public health are, therefore, leading to changes in both health and policy frontiers across the globe. These trends – from telemedicine to increasing social inequalities – require a more flexible approach to public health and the latter’s regulation. This paper aims to identify and analyze various important new directions in public health and discuss how these could affect policy. It examines phenomena such as the emergence of digital health solutions, the impact of SDOH as a key driver of health, and various threats, including pandemics, NTDs, and evolving environments that are reshaping health needs and concerns. From a literature review of the extant literature and qualitative policy analysis, the paper seeks to outline the limitations of current public health policy and policy responses and offer relevant policy advice. Based on these key findings, engaging technology can unlock enhanced health success and perpetuity but faces digital and social exclusion barriers. Also, new challenges of global health risks like COVID-19 revealed the importance of decoupling and the use of volatile, adaptable policies. In conclusion, the paper calls for the domestication of emerging trends into policy while promoting the cardinal pillars of health policy, which include inclusion, innovation, and international cooperation.